Highly durable photoelectrochemical H2O2 production via dual photoanode and cathode processes under solar simulating and external bias-free conditions. Issue 6 (29th January 2020) - Jeon, Tae Hwa; Kim, Hyejin; Kim, Hyoung-il; Choi, Wonyong
Abstract : A phosphate (P)- and Mo-modified BiVO4 photoanode and AQ-modified carbon cathode achieve efficient and durable photoelectrochemical production of H2 O2 through dual processes. Abstract : This study demonstrated efficient solar-to-H2 O2 conversion through a photoelectrochemical (PEC) cell that maximizes the utilization of solar energy by having double side generation of H2 O2 on both the photoanode and cathode. This work was accomplished by preparing (i) efficient BiVO4 (BVO) photoanodes modified with various metal dopants (Mo, W, or Cr), (ii) surface-treatment with phosphate on the as-synthesized photoanodes, and (iii) single-walled carbon nanotube (CNT) electrodes with anchored anthraquinone (AQ-CNT), a reversible H2 O2 -evolving catalyst that has been widely used in the H2 O2 production industry. The introduction of Mo into BVO and surface phosphate treatment on BVO (P-Mo-BVO) enhanced the faradaic efficiency (FE) of H2 O2 production from water oxidation and slowed the H2 O2 decomposition kinetics with achieving highly durable PEC reactions over 100 h (90% photocurrent remained), while bare Mo-BVO experienced the rapid decline of the photocurrent during irradiation with the dissolution of BiVO4 . The utilization of AQ on the cathode made the H2 O2 production by oxygen reduction highly selective and suppressed competing H2 production completely. Consequently, the optimized configuration of a BVO photoanode modified with Mo (10 atom%) and phosphate and an AQ-CNT cathode enabled H2 O2 production on both electrodes, yielding H2 O2 production with FE values of 40–50% and ∼100%, respectively, across a broad range of potentials (0.75 to 2 VRHE ) and a net H2 O2 production rate of 0.66 μmol min −1 cm −2 at 1.0 VRHE . This dual electrode system also successfully demonstrated H2 O2 production under an external bias-free condition with a net H2 O2 production rate of 0.16 μmol min −1 cm −2 and FE value of ∼43% and ∼100% for photoanodic and cathodic production, respectively. To the best of our knowledge, this is the most durable PEC system for H2 O2 production obtained using a BiVO4 -based photoanode that enabled the simultaneous photoanodic and cathodic production of H2 O2 .